Development of biocompatible natural polymer as promising green emissaries of essential therapeutics-A brief overview - Kunal Pal (International Journal of Vascular Surgery and Medicine - Peertechz Publications, 2020)
Most of the natural polymers are high molecular weight; water soluble polymers made up of monosaccharide units and joined by different kinds of linkages [1]. Gummy exudates of natural polymers such as protein, enzyme, muscle, fiber, and polysaccharide have been used to formulate various pharmaceutical products [2,3]. Natural polymers have advantages over the synthetic ones because they are chemically inert, nontoxic, economic, biodegradable and abundantly available. Natural polymers such as polysaccharides are hydrophilic, enzymatically degradable, and are able to retain the stability of protein drugs incorporated in them as well as increase their (proteins) therapeutic effects [4].